2016
DOI: 10.1371/journal.pone.0164976
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent and Multipotent Stem Cells Display Distinct Hypoxic miRNA Expression Profiles

Abstract: MicroRNAs are reported to have a crucial role in the regulation of self-renewal and differentiation of stem cells. Hypoxia has been identified as a key biophysical element of the stem cell culture milieu however, the link between hypoxia and miRNA expression in stem cells remains poorly understood. We therefore explored miRNA expression in hypoxic human embryonic and mesenchymal stem cells (hESCs and hMSCs). A total of 50 and 76 miRNAs were differentially regulated by hypoxia (2% O2) in hESCs and hMSCs, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
(74 reference statements)
0
8
0
Order By: Relevance
“…Interestingly, a variant in the apolipoprotein C-III ( APOC3 ) gene was found to create a miR-4271 binding site in the corresponding mRNA, which was associated with lower plasma triglycerides, potentially increasing risk of coronary heart disease 50 . Other studies demonstrated that miR-4271 expression was upregulated in the plasma of smokers in comparison to nonsmokers 51 and following hypoxia in human embryonic stem cells 52 , suggesting that miR-4271 may be responsive to environmental stressors though its function in human milk remains unknown. The second most highly expressed miRNA in human milk EVs, miR-3197, has been suggested to be semen-specific in forensic studies 53 , 54 , however, miR-3197 expression was detected in human mesenchymal stem cells 55 , human placenta 56 , serum from patients with hepatocellular carcinoma 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a variant in the apolipoprotein C-III ( APOC3 ) gene was found to create a miR-4271 binding site in the corresponding mRNA, which was associated with lower plasma triglycerides, potentially increasing risk of coronary heart disease 50 . Other studies demonstrated that miR-4271 expression was upregulated in the plasma of smokers in comparison to nonsmokers 51 and following hypoxia in human embryonic stem cells 52 , suggesting that miR-4271 may be responsive to environmental stressors though its function in human milk remains unknown. The second most highly expressed miRNA in human milk EVs, miR-3197, has been suggested to be semen-specific in forensic studies 53 , 54 , however, miR-3197 expression was detected in human mesenchymal stem cells 55 , human placenta 56 , serum from patients with hepatocellular carcinoma 57 .…”
Section: Discussionmentioning
confidence: 99%
“…They do not code proteins, but regulate post-transcriptional and translational gene expression. These molecules have multiple actions contributing to diverse normal and pathological cellular processes, including cell death, development, metabolism, neuronal patterning and oncogenesis (Pocock, 2011; Yu et al, 2012; Agrawal et al, 2016). Research indicates that a group of microRNAs are regulated by HIF-1, and in other instances, HIF-1 is the target of microRNAs.…”
Section: The Role Of Hypoxia-regulated Micrornas In Cancer Metabolismmentioning
confidence: 99%
“…6 b). We also screened Nor-EVs or Hypo-EVs for several known anti-inflammatory and anti-remodeling miRNAs including let-7, miR-485, miR-29b, and miR-30a [ 37 ], which are regulated under hypoxia in MSCs [ 18 , 38 ]. Intriguingly, among the miRNAs, miR-146a-5p was the most abundant in Nor-EVs or in Hypo-EVs (see Additional file 3 ).…”
Section: Resultsmentioning
confidence: 99%